SENP1 and SENP2 regulate SUMOylation of amyloid precursor protein. Issue 4 (April 2018) - Maruyama, Takuma; Abe, Yoichiro; Niikura, Takako
Abstract: Amyloid β, a key molecule in the pathogenesis of Alzheimer's disease (AD), is produced from amyloid precursor protein (APP) by the cleavage of secretases. APP is SUMOylated near the cleavage site of β-secretase. SUMOylation of APP reduces amyloid β production, but its regulatory system is still unclear. SUMOylation, a modification at a lysine residue of a target protein, is mediated by activating, conjugating, and ligating enzymes and is reversed by a family of sentrin/SUMO-specific proteases (SENPs). Here, we found that both SENP1 and SENP2 induced de-SUMOylation of APP. Using quantitative PCR, we also found that expression of SENP1 but not SENP2 increased in an age-dependent manner only in female mice. The results of immunoblot analyses showed that the protein expression was consistent with the PCR results. Females, compared to males, have a higher incidence of AD in humans and show more aggressive amyloid pathology in AD mouse models. Our results provide a clue to understanding the role of SUMOylation in the sex difference in AD pathogenesis.